Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-020-72722-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating PM2.5 responses to other air pollutants and meteorological factors across multiple temporal scales

Abstract: It remains unclear on how PM2.5 interacts with other air pollutants and meteorological factors at different temporal scales, while such knowledge is crucial to address the air pollution issue more effectively. In this study, we explored such interaction at various temporal scales, taking the city of Nanjing, China as a case study. The ensemble empirical mode decomposition (EEMD) method was applied to decompose time series data of PM2.5, five other air pollutants, and six meteorological factors, as well as thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 30 publications
3
16
1
Order By: Relevance
“…Thereafter, based on the defined time series, the six parameters of NO 2 , SO 2 , CO, HCHO, O 3 , and AI from Sentinel-5P, and the DEM product from SRTM were extracted and averaged for the model training. Regarding Sentinel-5P data, we selected CO and HCHO due to their similar emission source to that of PM 2.5 [48][49][50][51], SO 2 and NO 2 as precursors for the PM 2.5 [51][52][53], and O 3 due to its varying interaction with PM 2.5 by seasons and regions [54][55][56]. Lastly, we also included the product of AI as an informative parameter about PM 2.5 [57], since it captures signals of aerosols emitted from biomass burning or fire events [58], which is another source of particulate matter [59,60].…”
Section: Data Collection and Reprojectionmentioning
confidence: 99%
“…Thereafter, based on the defined time series, the six parameters of NO 2 , SO 2 , CO, HCHO, O 3 , and AI from Sentinel-5P, and the DEM product from SRTM were extracted and averaged for the model training. Regarding Sentinel-5P data, we selected CO and HCHO due to their similar emission source to that of PM 2.5 [48][49][50][51], SO 2 and NO 2 as precursors for the PM 2.5 [51][52][53], and O 3 due to its varying interaction with PM 2.5 by seasons and regions [54][55][56]. Lastly, we also included the product of AI as an informative parameter about PM 2.5 [57], since it captures signals of aerosols emitted from biomass burning or fire events [58], which is another source of particulate matter [59,60].…”
Section: Data Collection and Reprojectionmentioning
confidence: 99%
“…It is worth noting that the correlation between PM 2.5 concentrations and temperature varies by several factors such as time scales, geographic regions and components of PM 2.5 . Fu et al reported the correlation between PM 2.5 levels and temperature was positive at the daily scale, but was negative at the monthly scale in China [ 47 ]. A multiple linear regression model used to analyze 11-year records in the US revealed positive relations between ambient PM 2.5 concentrations and temperature with varied strengths across regions [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, airborne culturable bacteria community was also found to be higher and positively correlated with particulate matter concentration and chemical composition in Asian dust events (Jeon et al 2011). Chemical components of aerosols, such as CO and CO 2 , have shown a higher positive correlation with the bacterial community, explaining approximately 55% of the variance (Innocente et al 2017) associated with firewood combustion (Fu et al 2020;Xu et al 2017;Zhong et al 2019;Li et al 2019). Our findings show that despite the high pollution and carbon concentration in particulate matter produced in Temuco during colder days and due to residential firewood combustion, the bacterial community can be detected, and its diversity increases with air quality deterioration.…”
Section: Relationship Between Environmental Factors and Airborne Bacterial Communitiesmentioning
confidence: 94%
“…Moreover, PM 10 and CO also exhibited strong positive correlations between them (R = 0.835) and strong negative with T (R = − 0.788, − 0.754). Fu et al (2020) showed that PM 2.5 is positively correlated with CO during polluted days in China. It is also commonly observed that the spatial distribution of CO and particulate matter concentration tends to be the same in most parts of the day (Wang et al 2017;Chuai and Feng 2019).…”
Section: Environmental Characteristics During Air Samplingmentioning
confidence: 99%